Understanding the link between type 2 diabetes mellitus and Parkinson’s disease: role of brain insulin resistance - Theodora Ntetsika; Sergiu-Bogdan Catrina; Ioanna Markaki (Neural Regeneration Research)
Type 2 diabetes mellitus and Parkinson’s disease are chronic diseases linked to a growing pandemic that affects older adults and causes significant socio-economic burden. Epidemiological data supporting a close relationship between these two aging-related diseases have resulted in the investigation of shared pathophysiological molecular mechanisms. Impaired insulin signaling in the brain has gained increasing attention during the last decade and has been suggested to contribute to the development of Parkinson’s disease through the dysregulation of several pathological processes. The contribution of type 2 diabetes mellitus and insulin resistance in neurodegeneration in Parkinson’s disease, with emphasis on brain insulin resistance, is extensively discussed in this article and new therapeutic strategies targeting this pathological link are presented and reviewed.